Effects of heat reflux extraction on the content, antioxidant, and immune activity of polyphenols and flavonoids from hempseed threshing residues - Xiao-Jun Li; Juan Guo; Yong-ping Xu; Shu-ying Li; Na Li; Qing-ye Liu (PLoS ONE, 2025)
Objective Hempseed threshing residues are rich in phytochemicals such as polyphenols and flavonoids. Phenolic and flavonoid compounds have been associated with antioxidant, antibacterial and anticancer activities. The re-use of the hempseed threshing residues as value-added materials is, not only cost-saving, but also environmentally beneficial. It is therefore important to develop an effective method for extraction of phenolic compounds and flavonoids from hempseed threshing residues. Methods In this investigation, the extraction of phenolic constituents and flavonoids from hempseed threshing residues using heat reflux extraction (HRE) were optimized through response surface methodology (RSM). Four HRE parameters to enhance the yield of crude extracts (CE), total phenolic content (TPC), and total flavonoids content (TFC) were evaluated. Additionally, the study evaluated the chemical compounds, antioxidant characteristics of the extracts, and the immune activity of the extracts was assessed by quantifying the levels of inflammatory cytokines, specifically IL-6, IL-10, and TNF-α. Results The best extraction parameters were determined as: for the extraction time of 69.71 min, a liquid-solid proportion of 5.12:1, a particle size of 1150 µm, and an ethanol concentration of 69.60%. Under these optimized conditions, the yields for CE, TPC, and TFC were 4.74%, 27.54%, and 16.02% respectively. The data conformed well to multiple regression models, showing that these extraction parameters markedly influence the yields of CE, TPC, and TFC. Most of the compounds found may belong to the class of polyphenol and flavonoids. Cellular assays indicated that extracts from hempseed threshing residue notably reduced pro-inflammatory factors (TNF-α, IL-6) and increased anti-inflammatory factors (IL-10) in RAW 264.7 cells. Conclusion This research lays a theoretical foundation for extracting polyphenols and flavonoids from hempseed threshing residue and for the comprehensive assessment of antioxidant and immune-enhancing products. However, the antioxidant and immune activity of hempseed threshing residues extracts under physiological conditions in vivo, and the relevant mechanism should be further studied.